Overall quality of life perception among occupants of green and non-green office buildings in Malaysia - Laiche, Abdelfatah Bousbia; Dahlan, Nur Dalilah; Shari, Zalina; Zaky Jaafar, Mohamad Fakri (Chulalongkorn University - Faculty of Architecture, 2023)
Indoor environmental quality (IEQ) has become an important component of building design because people tend to spend the majority of their time indoors. The main purpose of this study is to investigate the occupants’ overall perceived Quality of Life (QoL) experience in two green and two non-green office buildings. All four buildings are situated in Klang Valley, Malaysia, and they are open-plan office buildings. 162 questionnaires were administered to assess the relationship between individuals' perceived QoL and IEQ factors. The IEQ factors, classified into ambient conditions, designed environment, and behavioural environment, are found to impact QoL. Findings from the case studies reveal that the four buildings varied in the aspect of Behavioural Environment, where some of the IEQ factors in the green buildings were perceived as slightly uncomfortable. It was also found that several IEQ categories interact as a system in which improvement of occupants' QoL experiences cannot be accomplished solely through the instrumental components of IEQ, as the designed and behavioural environments have substantial impacts. Several missing factors linked to the Green Building Index (GBI) criteria were significantly correlated with the QoL experience of occupants.